Effective Use of Lexical Categorization in Vocabulary Development Using Short Stories among Arab Female Learners - Shakeel, Farah; Kheri, Nahid Awad; Tariq, Saba; Mohammed, Abdulwahab Mohammed Saeed (مجلة العلوم التربوية والدراسات الإنسانية سلسلة الآداب والعلوم التربوية والإنسانية والتطبيقية, 2023)
There are clear variations in the connotations and linguistics of Arabic and English languages. It has been observed that Arab learners study English as a functional language which does not expose them to the literature of English. As a result, the concept of English as a language emerges in an extremely concise and confined area of study for them. The purpose of this research was to identify the process of acquisition of lexical items amongst the Arab female learners. The subjects were students studying Short Stories in the Bachelor's program of English. The technique used to conduct the research was a blend of qualitative and quantitative method. To collect the data a post-test and pre-test was administered. Also, a closed ended questionnaire was distributed to collect responses from the subjects of study. The study aimed at providing solutions to the problem of low vocabulary among English language learners. The outcome of the current research holds a strong significance as the findings are impressively motivating for teachers using literature to develop language acquisition. Though the end results show a minimal decrease of 3% in incorrect responses after getting acquainted with lexical items used in pre-test, a sharp fall of 60% is seen in overall incorrect answers after collecting the data through lexical categorization. It is expected that if the technique of lexical categorization is used and the suggestions given here are implemented, the learners will be able to correctly use vocabulary items in a variety of contexts in various situations.